A highly sensitive design of subwavelength grating double-slot waveguide microring resonator. (28th May 2020) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: We presented a novel design of a microring resonator based on a subwavelength grating (SWG) double-slot waveguide (WG) due to its enhanced sensitivity. The paper is divided into two parts. In the first part, we studied and compared the modal characteristics of SWG ridge, single-slot and double-slot WGs. A large value of 0.78 for overlap intensity integration in the upper cladding for SWG double-slot WG is obtained which is a positive sign for designing highly sensitive devices. In the later section, the spectral characteristics of a ring resonator based on the above-mentioned WGs are modelled and spectral characteristics are analyzed. The results demonstrated the clear dominance of a SWG double-slot WG ring resonator over the remaining two WG schemes. At optimized sensor design, the best sensitivity of 840 nm RIU −1 is obtained. To the best of our knowledge, we believe that the sensitivity acquired in this paper is the highest compared to the previously reported values in the literature based on SWG silicon WG sensors.